Analysis on the situation of agricultural holdings in the context of the end of the first programming period (2007-2013) - Ana-Ruxandra Micu; Dana Rebega; Gabriela Gimbăşanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
One of the main problems of Romania, which appeared immediately after the revolution of 1989 has represented by an excessive fragmentation of agricultural land, accounting and currently an issue that is trying to be remedied by different measures to encourage through the pooling of agricultural exploitations. Farms in Romania, very many are also characterized by the low productivity are concentrated holdings of subsistence and semi-subsistence farmers barely that can provide the necessary products for their own use, so that did not enter into question whether commercialization of products in order to obtain revenue.
Keywords: 330; farms; subsistence and semi-subsistence production value standard